2022
DOI: 10.1093/infdis/jiac340
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Injury in Ugandan Children Hospitalized With Malaria

Abstract: Background Severe malaria is associated with multiple organ dysfunction syndrome (MODS), which may involve the gastrointestinal tract. Methods In a prospective cohort study in Uganda, we measured markers of intestinal injury (intestinal fatty-acid binding protein, I-FABP, and zonula occludens-1, ZO-1), and microbial translocation (lipopolysaccharide binding protein, LBP, and soluble complement of differentiation 14, sCD14) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Remarkably, Ngai and colleagues ( 16 ) recently published a similar study that complements, validates, and further expands the findings of Sarangam et al The biomarkers I-FABP, LBP, and sCD14 (in addition to zonula occludens-1 [ZO-1], another marker of intestinal injury) were studied in a different cohort of 523 Ugandan children hospitalized with SM. That study showed that severe intestinal injury, defined slightly differently (i.e., I-FABP levels of ≥5.6 ng/mL), was present in 1 out of every 10 sick children.…”
Section: Commentarymentioning
confidence: 54%
“…Remarkably, Ngai and colleagues ( 16 ) recently published a similar study that complements, validates, and further expands the findings of Sarangam et al The biomarkers I-FABP, LBP, and sCD14 (in addition to zonula occludens-1 [ZO-1], another marker of intestinal injury) were studied in a different cohort of 523 Ugandan children hospitalized with SM. That study showed that severe intestinal injury, defined slightly differently (i.e., I-FABP levels of ≥5.6 ng/mL), was present in 1 out of every 10 sick children.…”
Section: Commentarymentioning
confidence: 54%
“…In other studies, associations between IFABP and inflammatory biomarkers have been found in malaria, but not in sepsis and cardiac surgery. 15 , 17 , 18 , 19 , 38 Further, IFABP has been convincingly associated with mortality after cardiac arrest, while IL-6 are among the few inflammatory biomarkers which are associated with poor outcome after adjustment for confounding factors. 9 , 39 , 40 , 41 , 42 , 43 , 44 Importantly, IFABP and inflammatory biomarkers could merely increase in parallel with the degree of whole-body ischaemia.…”
Section: Discussionmentioning
confidence: 95%
“… 12 , 13 , 14 , 15 However, there are few reports investigating the associations between intestinal injury and systemic inflammatory biomarkers in general. 15 , 16 , 17 , 18 , 19 Previously, we have reported that both IFABP and some of the analysed inflammatory biomarkers, including interleukin (IL)-6 and the terminal complement complex (TCC), were associated with multiple organ dysfunction and mortality after out-of-hospital cardiac arrest (OHCA). 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…Regenerating islet-derived protein 3A (Reg3a) is a bactericidal, gut-specific protein that is often secreted in response to inflammation during the acute phase of infection to protect the gut epithelium [ 21 , 22 ]. Intestinal fatty acid-binding protein 2 (iFABP) is another small intestine-specific protein that is involved in the metabolism of long-chain fatty acids and can be used as a marker for gut injury [ 23 ].…”
Section: Introductionmentioning
confidence: 99%